Interference issues and mitigation method in WSN 2.4GHz ISM band: A survey - Azmi, N.; Kamarudin, L. M.; Mahmuddin, Massudi; Zakaria, Azizi; Shakaff, A. Y. M.; Khatun, S.; Kamarudin, K.; Morshed, M. N. (2014)
Current lifestyles promote the development and advancement in wireless technologies, especially in Wireless Sensor Networks (WSN) due to its several benefits.WSN offers a low cost, low data rate, flexible routing, longer lifetime, and low-energy consumption suitable for unmanned and long term monitoring.Among huge WSN applications, some key applications are smart houses, environmental monitoring, military applications, and other monitoring applications.As a result, ubiquitous increase in the number of wireless devices occupying the 2.4GHz frequency band.This causes a dense wireless connection followed by interference problem to WSN in the 2.4GHz frequency band. WSN is most affected by the interference issue because it has a lower data rate and transmission power compared to WLAN.Despite efforts made by researchers, to the author's knowledge, the interference issue is still a major problem in wireless networks.This paper aims to review the coexistence and interference issues of existing wireless technologies in the 2.4GHz Industrial, Scientific and Medical (ISM) band.Keywords— Coexistence, Frequency Spectrum, IEEE 802.15.4, Interference, WSN, 2.4GHz ISM band